1984
DOI: 10.1002/pssa.2210860147
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties and optical absorption of SnSe evaporated thin films

Abstract: Resistivity, Hall effect, and optical absorption coefficient measurements are performed on SnSe evaporated thin films. The resistivity decreases with increasing temperature whereas the Hall mobility and carrier density increase with increasing temperature. An exponential 1/T law is observed for each of these variations. The results are explained in terms of a grain boundary potential barrier mechanism. The optical absorption coefficient is measured at 300 K over the photon energy range 0.8 to 1.3 eV. An analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…(113), (020), (203), which confirms the polycrystalline nature of the film. A similar preferred orientation of grains along the (111) plane in SnSe film was observed in the evaporated SnSe thin films by Bhatt et al [15] and by Dang Tran Quan [16]. On the other hand, H. Chandra et al [17] had observed (400) diffraction plane for films grown by flash evaporation technique and Teghil et al [18] had reported orientation of grains along (011) and (200) Diffraction Standards (JCPDS) data card [19].…”
Section: Resultssupporting
confidence: 51%
“…(113), (020), (203), which confirms the polycrystalline nature of the film. A similar preferred orientation of grains along the (111) plane in SnSe film was observed in the evaporated SnSe thin films by Bhatt et al [15] and by Dang Tran Quan [16]. On the other hand, H. Chandra et al [17] had observed (400) diffraction plane for films grown by flash evaporation technique and Teghil et al [18] had reported orientation of grains along (011) and (200) Diffraction Standards (JCPDS) data card [19].…”
Section: Resultssupporting
confidence: 51%
“…The optical transmittance decreases on annealing. Since the absorption coefficient is very large and it is measured at room temperature, the presence of the indirect band gap as in the case of the bulk sample is improbable [16,17]. It is reasonable to consider that the absorption of SnSe evaporated thin films is due to an allowed direct transition from the top of the valence band to the bottom of the conduction band at the centre of the Brillouin zone.…”
Section: Snse Thin Filmsmentioning
confidence: 99%
“…NbSe 2 is metallic [27][28][29][30] with room temperature ab-plane resistivity values between 1.5 μΩ-m -36 μΩ-m reported [27][28][29]. As a binary, SnSe is a p-type semiconductor [31] with significantly higher room temperature resistivity values of 4×10 4 μΩ-m -1.8×10 6 μΩ-m for bulk samples [32] and 1.0×10 5 μΩ-m -2.0×10 6 μΩ-m for polycrystalline thin films [33] [34]. The simplest approximation is to assume that only the NbSe 2 layer conducts, as was done previously for the MLC.…”
Section: Atom Parametersmentioning
confidence: 99%